PENGGUNAAN LAYANAN GO KAMPUS (GOPUS) SEBAGAI BAGIAN DARI GAYA HIDUP MAHASISWA RANTAU UINSU MEDAN DI ERA DIGITAL - Suci Aulia Ramadan S; Findyani Siregar; Alya Dwi Ananta; Amanda Natasya Gunawan; Miftahurrahmah Elhayatli (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
The development of digital technology has brought significant changes in the lifestyle of students, especially students from other regions who need easy access to campus services and daily needs. One of the increasingly popular innovations is the Go Campus (GOPUS) service, which has become part of the lifestyle of students in the midst of this digital era. This study aims to describe in depth the use of the Go Campus (GOPUS) service as part of the lifestyle of students from other regions of the State Islamic University of North Sumatra (UINSU) Medan in the digital era, focusing on their experiences, motivations, and impacts on their lives. This study uses a qualitative approach with a descriptive research type. Data were collected through in-depth interviews with four UINSU students from other regions who use GOPUS, participant observation, and documentation. Data were analyzed thematically based on patterns of use and students' perceptions of the service. The results of the study indicate that GOPUS has become an integral part of the lifestyle of UINSU students from other regions, providing practical solutions to transportation and time constraints. The main motivations for using GOPUS include convenience and practicality, especially in bad weather conditions or when assignments are piling up. The use of this service facilitates daily activities but also affects their physical activity patterns, with the potential to support a sedentary lifestyle. Although most respondents were satisfied, there were complaints related to service delays and driver availability and response speed. It was concluded that GOPUS not only meets functional needs, but also reflects students' adaptation to the social and technological environment.